Direct Regional Head Elections and Excessive Corruption Loopholes - Susdarwono, Endro Tri; Surahmadi, Surahmadi (Center for Maritime Policy Governance Studies (CMPGS), 2025)
Corruption remains one of the most pressing challenges undermining democracy, governance, and public trust in Indonesia, particularly following the implementation of decentralization and regional autonomy. While regional autonomy was intended to bring prosperity and equal development, in practice it has often facilitated the spread of corrupt practices from central government to regional administrations. The issue has become more acute with the implementation of direct regional head elections (pilkada), which, though designed to strengthen democratic participation, have created significant financial and political pressures on candidates, often resulting in the misuse of state budgets and the normalization of money politics. This study aims to examine the relationship between direct regional elections and the proliferation of corruption loopholes, highlighting how electoral mechanisms inadvertently encourage corrupt behavior. The research employs a descriptive explorative method, relying on secondary data from scholarly works, official documents, and prior research, and analyzing them through qualitative descriptive analysis to uncover patterns and systemic weaknesses. The findings indicate that direct elections, while enhancing political legitimacy, also generate high financial demands that compel candidates to seek external funding, leading to post-election corruption through budget manipulation, project markups, politicization of social assistance, and collusion between bureaucrats, legislatures, and political investors. Moreover, the system often fails to ensure accountability, as legislative oversight is weak and public mechanisms for monitoring leaders remain limited. The study concludes that although direct elections provide opportunities for citizen participation, they also institutionalize structural vulnerabilities that sustain corruption. This paradox underscores the need for reforms in electoral financing, stricter accountability mechanisms, and stronger institutional checks and balances to prevent democracy from becoming a breeding ground for corruption.